Brusatol increases chemotherapeutic drug efficacy in pancreatic ductal adenocarcinoma by suppressing Nrf2 signaling - Juan Zhang; Hongxi Xu; Yulin Wu; William Chi Shing Cho; Yang Li; Peiyao Ren; Yanfang Xian; Zhixiu Lin (Compuscript Ltd, 2024)
Chemoresistance to gemcitabine (Gem) remains a substantial obstacle in the treatment of pancreatic ductal adenocarcinoma carcinoma (PDAC). Nrf2, a transcription factor responsive to oxidative stress, has been implicated as a key contributor to chemoresistance. Previous studies have demonstrated anti-tumor effects of brusatol (BRT) in PDAC. Herein, we aimed to investigate the efficacy of BRT in enhancing chemosensitivity to Gem and to elucidate the underlying mechanisms involving Nrf2. Gain- and-loss-of-function experiments revealed that Nrf2 exacerbated Gem chemoresistance in PDAC cells. Additionally, BRT effectively inhibited PDAC cell proliferation and enhanced Gem chemosensitivity. Mechanistic investigations demonstrated that BRT sensitized PDAC cells to Gem by suppressing Nrf2 at the transcriptional level. Activation of Nrf2 conteracted BRT's effects on chemosensitivity. In contrast, combination treatment with Nrf2 silencing and BRT demonstrated a more potent inhibitory effect on Gem in vitro and in vivo, thereby indicating the Nrf2 dependence of BRT action. These findings highlight BRT's ability to enhance Gem chemosensitivity by inhibiting Nrf2 signaling in PDAC; therefore, BRT may serve as a potential adjuvant therapy for PDAC.